Effects of Thallium–Aluminum‐Codoped Zinc Oxide Thin Film as a New Transparent Conducting Oxide. Issue 9 (8th March 2021) - Zamani Meymian, Mohammad-Reza; Mousavi, Mir-Ali; Rabbani, Mahboubeh; Fallah, Milad
Abstract : Herein, the electro–optical properties of sol–gel spin‐coated "thallium–aluminum‐codoped zinc oxide (TAZO)" focusing on the effects of thallium are investigated. It is shown that the amount of thallium (Tl) has a significant effect on improving the electrical properties of TAZO as a new transparent conducting oxide (TCO). The optimum results are achieved by adding 1 at% of Tl to aluminum‐doped zinc oxide (AZO), after which the sheet resistance ( R s ) value is reduced from 30.21 to 2.832 KΩ sq −1 . Although less R s is recorded in all amounts of Tl used (from 1 to 4 at%) than in Tl‐free samples, R s also increases as the amount of Tl increases, which is related to the degradation of the crystal structure at higher values of Tl. In view of a trade‐off between electrical conductivity and optical transparency, a decrease in transparency in the presence of Tl is a predictable issue, but while the Tl‐free samples record 90% transparency, the uniform thin film of 1 at% Tl‐AZO is able to achieve 85% transparency. This small amount of reduction in transparency shows the high potential of Tl to improve the properties of AZO as a TCO. Abstract : In this article, the influences of thallium dopingon structural, electrical, and optical properties of sol–gel‐derived Al‐doped ZnO thin film (TAZO) are investigated. Using spin‐coating method, 1 at% of thallium as a new dopant alongside 1 at% of aluminum shows a very large effect on improving the electrical properties of zinc oxide as a transparent conducting oxide such that it reduces the sheet resistance from 30 to 2.8 KΩ sq −1 .